2011
DOI: 10.1186/1472-6963-11-270
|View full text |Cite
|
Sign up to set email alerts
|

An intervention to improve care and reduce costs for high-risk patients with frequent hospital admissions: a pilot study

Abstract: BackgroundA small percentage of high-risk patients accounts for a large proportion of Medicaid spending in the United States, which has become an urgent policy issue. Our objective was to pilot a novel patient-centered intervention for high-risk patients with frequent hospital admissions to determine its potential to improve care and reduce costs.MethodsCommunity and hospital-based care management and coordination intervention with pre-post analysis of health care utilization. We enrolled Medicaid fee-for-serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 14 publications
4
79
0
1
Order By: Relevance
“…In line with studies elsewhere (11,14,(46)(47)(48)(49) it was found that inpatient treatment costs accounted for most of the overall expenditures, while the proportions differed by data source before (SR = 48.46% vs. AR = 69.46%), and after admission (SR = 52.57% vs. AR = 75.42%). Outpatient health service costs contributed the second largest share at T0 (SR = 33.83% vs. AR = 15.66%) while at T1, according to self-report, costs for medication and outpatient service were about equal (24.19% and 23.24% respectively).…”
Section: Self-report Vs Administrative Datasupporting
confidence: 65%
“…In line with studies elsewhere (11,14,(46)(47)(48)(49) it was found that inpatient treatment costs accounted for most of the overall expenditures, while the proportions differed by data source before (SR = 48.46% vs. AR = 69.46%), and after admission (SR = 52.57% vs. AR = 75.42%). Outpatient health service costs contributed the second largest share at T0 (SR = 33.83% vs. AR = 15.66%) while at T1, according to self-report, costs for medication and outpatient service were about equal (24.19% and 23.24% respectively).…”
Section: Self-report Vs Administrative Datasupporting
confidence: 65%
“…The review built on an existing evidence synthesis, prepared by the VA's EvidenceBased Synthesis Program Coordinating Center. 11 Researchers 14,16,18,[21][22][23][30][31][32][33] and with review articles describing healthcare delivery interventions for patients with complex chronic illnesses. [34][35][36] The review incorporated key findings, study design, and implementation strategies, 37 and was discussed with facility leadership to identify common elements of successful programs that would be viable and effective within the VA environment and at the local facility.…”
Section: Methodsmentioning
confidence: 99%
“…Robust evaluations may require staged interventions or randomization, long follow-up duration, and patient and staff surveys to determine effects, adding cost and time beyond the already expensive clinical efforts. [21][22][23] Partnered research-collaboration between researchers, operational leaders, and clinicians-is a unique approach to program development that may facilitate rapid healthcare redesign and implementation, while allowing for rigorous evaluation and testing. The VA has a rich tradition of sponsoring intramural partnered research, dating back to the development of the Quality Enhancement Research Initiative in the 1990s, 24 and these partnerships have been associated with substantial quality improvement achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent emergency service attendance has been associated with frequent contact with other health and social services (Kerr et al, 2005;Raven, Doran, Kostrowski, Gillespie, & Elbel, 2011;Thanacoody, Jay, & Sherval, 2009). Identifying emergency service users who also use other services may help identify those at risk.…”
Section: Introductionmentioning
confidence: 99%